2011
DOI: 10.1128/jvi.00503-11
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Changes in the Virus Capsid Permit Coxsackievirus B3 To Bind Decay-Accelerating Factor

Abstract: Many coxsackievirus B isolates bind to human decay-accelerating factor (DAF) as well as to the coxsackievirus and adenovirus receptor (CAR). The first-described DAF-binding isolate, coxsackievirus B3 (CB3)-RD, was obtained during passage of the prototype strain CB3-Nancy on RD cells, which express DAF but very little CAR. CB3-RD binds to human DAF, whereas CB3-Nancy does not. To determine the molecular basis for the specific interaction of CB3-RD with DAF, we produced cDNA clones encoding both CB3-RD and CB3-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 35 publications
(28 reference statements)
3
46
0
Order By: Relevance
“…In the new structure, each DAF molecule was found to link two adjacent protomers of the virus capsid in a mode of DAF binding different from that described previously for echoviruses 7 and 12 (4,22,43,45). Here, we present evidence that the new DAF footprint on the surface of CVB3-RD includes viral residues recently reported to be critical for DAF binding (41). More than 75% of the DAF interactions involve SCR2, which is known from previous SCR deletion studies to be essential for DAF binding by CVB3-RD (3).…”
mentioning
confidence: 55%
“…In the new structure, each DAF molecule was found to link two adjacent protomers of the virus capsid in a mode of DAF binding different from that described previously for echoviruses 7 and 12 (4,22,43,45). Here, we present evidence that the new DAF footprint on the surface of CVB3-RD includes viral residues recently reported to be critical for DAF binding (41). More than 75% of the DAF interactions involve SCR2, which is known from previous SCR deletion studies to be essential for DAF binding by CVB3-RD (3).…”
mentioning
confidence: 55%
“…For experiments with DAF transgenic mice, we wanted to use a DAFbinding isolate that replicated efficiently in mice. We therefore tested CVB3 H3-RD, a DAF-binding derivative of the cardiovirulent isolate CVB3 H3 which differs from CVB3 H3 in only a single capsid residue (21). After inoculation with 10 5 PFU by the intraperitoneal route, CVB3 H3-RD replicated to high titers in the pancreas, liver, and heart ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next determined whether DAF was required to facilitate apical CVB infection of BeWo cells, as has been shown for other polarized cell types (9,13). First, we compared the efficiency of apical infection by a non-DAF binding CVB isolate (CVB3-Nancy) versus a DAF-binding isolate (CVB3-RD) (a single amino acid difference exists between CVB3-RD and CVB3-Nancy [49]). We found that CVB3-Nancy infected BeWo cells poorly from the apical surface (Ͻ10%) compared to CVB3-RD, indicating that DAF was necessary for efficient apical infection of these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%